EFFECTS OF GLYPHOSATE ON GERMINATION AND PHOTOSYNTHESIS IN Prosopis alba G.: A BIOCHEMICAL APPROACH - Meloni, Diego Ariel; Nieva, María José; Martínez, Carlos Alberto (Biofix Scientific Journal, 2022)
In recent decades, the phytogeographic region of the Western Chaco has been subjected to heavy deforestation. The native forest was gradually replaced by agricultural crops using high doses of herbicides. Glyphosate is the most widely used herbicide, and its impact on the surrounding native flora is unknown. The aim of this work was to determine the effect of glyphosate on the germination of Prosopis alba seeds and the photosynthesis of seedlings. Seeds were placed between paper towels, moistened with solutions of 0, 10, 20, 20, 30 and 40 mg a.i. glyphosate l-1, in a growth chamber at 25 oC and a 12 h photoperiod. The percentage of germinated seeds and the mean germination time were calculated. The respiratory rate was measured in these seeds, and the activity of complexes I and III of the respiratory chain was quantified. The shikimate concentration and antioxidant response of the seeds were also quantified. Chlorophyll a fluorescence emission variables were measured in the cotyledons. It was concluded that glyphosate inhibits germination in P. alba seeds and decreases the speed of the process. This effect can partly be explained by inhibition of respiration, mainly at the level of complex III of the mitochondrial electron transport chain. It is also due to oxidative stress produced by the herbicide, since the antioxidant response of the seeds fails to compensate for the high production of reactive oxygen species. Glyphosate inhibits the photochemical stage of photosynthesis on P. alba cotyledons.